ANALISIS BALANCE SCORECARD UNTUK PENILAIAN KINERJA BUMNAG DALAM PENINGKATAN PENDAPATAN ASLI NAGARI SUNGAI TARAB - Saleh, Sri Madona; Khairunnisa, Tasya (Jurnal Akuntansi Syariah (JAkSya), 2025)
This study aims to determine the performance of BUMNag Bungo Satangkai Nagari Sungai Tarab using the Balanced Scorecard method by using 4 financial perspectives, customer perspectives, internal business perspectives, and growth and learning perspectives, in an effort to increase Nagari Original Revenue. This type of research is using a mixed method approach by analysing financial reports and interview results from BUMNag Bungo Satangkai. The data sources used in this study are primary data sources and secondary data. Primary data sources were obtained through interviews and secondary data sources were obtained from the financial statements of BUMNag Bungo Satangkai. informants and this research are the Chairman of BUMNag Bungo Satangkai, the secretary of BUMNag Bungo Satangkai and the Treasurer of BUMNag Bungo Satangkai. The results of this study indicate that the performance of BUMNag in a balanced scorecard with a total final score of BUMNag Bungo Satangkai of 78% is very healthy with category A.